Neural Mechanisms Mediating the Cross Education of Motor Function: Implications for Healthy Older Adults - Calvert, Glenn Hans (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2022)
Cross education (CE) is the process whereby a regimen of unilateral limb training engenders bilateral improvements in motor function. It is widely held that the contralateral gains thus derived may impart therapeutic benefits for patients with unilateral deficits arising from orthopaedic injury or stroke. Despite this prospective therapeutic utility, there exists remarkably little consensus concerning the mechanistic basis of this interlimb effect. The precise means through which the neuroanatomical structures and cellular processes that mediate CE may be influenced by age-related neurodegeneration are also almost entirely unknown. Notwithstanding the increased incidence of unilateral impairment in later life, age-related variations in the expression of CE have been examined only infrequently. In seeking to address these lacunae, the aim of this thesis was twofold: i) to examine age-related variations in the extent to which the phenomenon of CE is manifested, and ii) to devise novel methods of non-invasive brain stimulation with which to elucidate the physiological mechanisms which mediate this effect. In Chapter 1, an extensive review of the literature was presented that detailed several pathways that exhibit the potential to mediate the neural adaptations that underlie the expression of CE. A specific emphasis was placed upon the extent to which associated brain structures and networks may be affected by the neurodegenerative processes that are a feature of ageing. Although various mechanisms were proposed, a particular emphasis was assigned to the potential functional contributions of interhemispheric interactions subserved by transcallosal projections between dorsal premotor cortex (PMd) and primary motor cortex (M1). In Chapters 2 and 3, two novel methods of non-invasive brain stimulation were developed and refined, with the view of probing excitatory and inhibitory interhemispheric interactions between these brain regions. The intent was to apply these methods subsequently in an investigation of CE that formed the basis of Chapter 4. In the first experimental study (Chapter 2), we assessed the feasibility of applying a short duration burst (6-500 ms) of transcranial alternating current stimulation (tACS) or transcranial random-noise stimulation (tRNS) unilaterally to M1, in order to potentiate the amplitudes of motor-evoked potentials (MEPs) elicited 6 ms later by transcranial magnetic stimulation (TMS) applied to the opposite M1. The aim of this approach was to devise a novel assay of interhemispheric facilitation (IHF) ? a notoriously capricious measure of interhemispheric function that is obtained classically with dual-coil TMS. As this effect has been examined only sparingly with magnetic conditioning of non-primary motor regions (and elicited with even greater scarcity), we decided that in seeking to establish proof of principle, and to facilitate comparisons with effects reported by dual-coil TMS studies, it was necessary to apply conditioning stimulation only to M1. In applying this methodology, IHF was obtained by conditioning M1 with a 30 ms (but not 100 or 500 ms) duration burst of 140 Hz tACS. The magnitude of this effect was within the range of values reported previously by dual-coil TMS studies. In circumstances in which 6-500 ms duration bursts of 670 Hz tACS or 100-640 Hz tRNS were applied, this effect was not however obtained. Although these findings suggest that conditioning M1 with short duration tACS may provide a means of eliciting IHF, the inconsistency with which the effect was observed across conditions (and indeed participants) indicates that more research is required to optimise fully the stimulation parameters with which this effect may be obtained. Consequently, the tACS-based methodology developed in Chapter 2 was not applied as an index of IHF in the investigation of CE undertaken in Chapter 4. In the second experimental study (Chapter 3), a novel method of eliciting interhemispheric inhibition (IHI) was devised, that incorporated a fully automated dual-coil adaptive threshold hunting (ATH) paradigm. Although by convention IHI is expressed as a percentage change in MEP amplitude when a test stimulus of fixed intensity is applied in the presence of conditioning stimulation, the ATH method quantifies IHI as the percentage change in stimulation intensity required to elicit a MEP of a pre-specified amplitude. The objective of this study was to define a range of stimulation parameters (i.e., conditioning stimulus intensities, interstimulus intervals, and test coil orientations) that can be used reliably to elicit PMd-M1 IHI. In applying these methods, PMd-M1 IHI was obtained with test stimuli that induced current flow in the posteroanterior (PA) direction but was conspicuously absent when anteroposterior stimuli were applied instead. The magnitude of IHI obtained with PA test stimuli tended to increase with conditioning stimulus intensity (90%, 110%, 130% of resting motor threshold) but did not vary by interstimulus interval (8, 10, 40 ms). In seeking to demonstrate that the ATH method yields outcomes similar to those obtained with conventional MEP-derived measures, we also collected measures of M1-M1 IHI. In doing so, we showed that the pattern of outcomes obtained with ATH-based measures of M1-M1 IHI was consistent with that obtained with classical IHI approaches. These measures of (PMd-M1) IHI were applied subsequently in the study of CE that formed the basis of Chapter 4. In the third (and final) experimental study (Chapter 4), a unimanual ballistic wrist extension paradigm was employed, in which young and older adults completed a single session of non-dominant limb training. The intent was to examine potential differences in the levels of CE attained by young and older adults both immediately and one-week following the initial training session. Consistent with previous studies, we found that following a single session of unimanual ballistic wrist extension training undertaken with the non-dominant limb, similar levels of CE (expressed in terms of relative improvement and interlimb transfer) were present in young and older adults. Somewhat surprisingly, and in contrast to previous studies, the raw accelerations exhibited by older volunteers tended to exceed, and in some cases were appreciably greater than, those exhibited by young adults. It is therefore possible that the sample of older adults recruited in the present study was not representative of older adults generally. Using methods developed in Chapter 3, we also sought to establish whether training-related changes in short- and long-latency PMd-M1 IHI were related to interindividual variations in CE. Due to substantial fluctuations in the amplitudes of ?control? MEPs (i.e., those obtained in the absence of conditioning stimulation) during the course of each IHI measurement, which deviated appreciably from the expected threshold hunting target (200 ?V), it was not however possible to ascribe any functional significance to the ostensive changes in IHI that were observed. More specifically, as it was not known whether equivalent populations of neurons were being stimulated by the test stimulus at each point of measurement (due to fluctuations in control MEP amplitude), we could not discern whether the observed changes in IHI were driven by training-related changes in the excitability of corticospinal projections from the untrained M1, or alterations in the level of inhibitory drive engendered by the contralateral PMd. As a consequence, an interpretation of the observed changes in IHI could not be provided. The thesis concludes with a discussion of the main findings and limitations of the works thus presented and offers recommendations that may inform the basis of future studies of CE.
APPROVED
Keywords: Non-invasive brain stimulation; Ageing; Motor control; Motor learning; Transcranial magnetic stimulation; Cross education; TMS